Wandering spleen leading to splenic torsion with gastric and pancreatic volvulus - Shen, Mary R (BMJ Case Rep, 2021)
This case highlights a 37-year-old woman with primary sclerosing cholangitis awaiting liver transplantation who presented with torsion of a wandering spleen with associated gastric and pancreatic volvulus. The patient underwent emergent exploratory laparotomy with splenectomy. She had an uncomplicated postoperative course and recovered well.